“Apertem os cintos... a viagem vai começar”: movimentos investigativos com representações sobre surdos/as em piadas do Youtube - Laureano, Elaine Reis (2022)
Faced with the new possibilities arising from digital culture, jokes can reproduce or evoke different representations related to deafness and deaf people. Based on Foucault (2011), in this work, the will to truth – which concerns themes manufactured in a particular moment in history, and which, being transitory, manifests itself in a diluted way in the meanings, in order to be taken as the truth itself – is related to the representations in jokes, in particular, in Libras and in Portuguese, that thematize deafness, which, camouflaged by humor, teach about places and roles to be occupied by the deaf in society. Thus, based on the perspectives of Cultural Studies and Deaf Studies, one sought to make visible the cultural disputes around the meaning that cross these jokes, with a view to answering the following question: in what way do jokes in Libras and Portuguese, produced/consumed on YouTube, operate as cultural pedagogies and represent deaf people? It is noticed that the jokes that thematize deafness in Libras and in Portuguese convey representations that imply different wills of truth. Taking this issue into account, the following general objective was thus achieved: to understand how jokes in Libras and Portuguese, produced/consumed on YouTube, operate as cultural pedagogies and represent deaf people, which unfolded into four specific objectives, namely: i. to map the representations of deaf people present in jokes posted on YouTube, from 2015 to 2020; ii. identify the conception(s) of deafness and the wills to truth that underlie these jokes; iii. examine the way(s) of being and living as a deaf person represented in these cultural pedagogies; and iv. to analyze the consumption of the content addressed in the jokes, based on the comments of internet users. After going through the path of a qualitative research, of the documentary type, anchored in Cultural Analysis, the thesis argument was confirmed, arriving at the idea that the jokes in Libras and Portuguese, produced/consumed on YouTube, operate as cultural pedagogies, presenting lessons based on conceptions of deafness that mark identities, such as that of deaf people; therefore, based on certain social and cultural views, they teach about ways of being and living as a deaf person, according to the language in which they are produced. In order to do so, the jokes produced in Portuguese resumed crystallized views in relation to the roles played and the places occupied by deaf people, representing them as inferior in relation to hearing people in the hierarchy of power relations and reinforcing the will to truth that the deaf person is incapable, for not hearing, and that their visual-spatial language is inferior to the auditory oral language that predominates in their country, while the jokes produced in Libras, in turn, affiliated with an antagonistic will to truth, affirmed the deaf people, through the bias of difference, identity and potentiality, as a people who have their own language and culture. Thus, the research showed that in the jokes produced in Portuguese, representations based on the clinical view that categorizes deafness as a disability prevailed, while in the jokes produced in Libras, the conception of deafness as a cultural difference predominated.